An Intellectual in the Embrace of Dystopia: the Plato Papers by Peter Ackroyd - Pavlović, Tomislav M. (Sinteze - časopis za pedagoške nauke , književnost i kulturu, 2024)
The aim of this paper is to analyze the transformation of the term intellectual, which is established as a kind of paradigm in modern and postmodern times. The focus of the research is first of all on the reduction of the role of the intellectual in modern times, which was echoed in the thoughts of numerous philosophers of modern and postmodern epoch. Then the postmodern dystopian novel Plato’s Papers by the English writer Peter Aykroyd, is analyzed. It is a dystopian work in which the aforementioned tendencies were given an artistic articulation. The hero of the novel Plato, as the research shows, represents a travestied image of the ancient philosopher Plato and acts in a modern telematized polis of the distant future. The works and fate of the postmodern Plato are articulated in the novel in a way that hints that escapism is the only possible answer to the challenges of the destructive relativizations of the postmodern era.